Some Results for Generalized Local Homology Modules - Tognon, Carlos Henrique (2025)
We prove some results on the finiteness of co-associated primes of generalized local homology modules inspired by the conjecture of Grothendieck and the question of Huneke. We also show equivalent properties of minimax local homology modules. Here, we get applications for the generalized local homology module, in a general theory of modules.